PENERAPAN PERCEPATAN LAYANAN PATEN SEDERHANA PADA UNDANG-UNDANG CIPTA KERJA - Ireyna Chaliva (Magister Hukum Universitas Semarang, 2023)
The purpose of this research is to describe the efforts made by the government to improve public services in the simple patent regime, along with the obstacles that arise after the issuance of accelerated simple patent applications in the. The focus of this research is that the establishment of the Job Creation Law provides various kinds of changes accompanied by pros and cons in society, especially the Intellectual Property sector in a simple patent regime that has changes to accelerate patent services. This research must be carried out so that the government can examine again the human resources capabilities of patent examiners and the importance of including the acceleration of simple patent services in the Patent Bill so that there is no overlap between other laws and regulations. The research method used in this research is normative juridical by examining legal norms accompanied by data obtained from interviews with internal parties at the Patent Legal Services Sub-Directorate, DJKI, through a statutory approach. This research concludes that by carrying out efforts to accelerate services on simple patents, which can increase PNBP, there will be a polemic regarding the human resources who carry out patent examinations where the number of them is not commensurate with the number of applications submitted each year and the short time that the government has applied, this will have an impact on the quality of the patents produced.